Implementation of the idea of lifelong learning in NGOs on the Polish-Czech-German borderland = Realizacja idei lifelong learning na pograniczu polsko-czesko-niemieckim w organizacjach pozarządowych (NGO) - Hojny, Paulina; Narkiewicz-Niedbalec, Ewa (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article addresses the issue of lifelong learning implemented by associations and foundations working in the spheres of education and culture on the Polish-Czech-German borderland and involving representatives of at least two of these neighbouring nations. The analysis involved eight such organizations. The authors indicated various theoretical conceptualizations of the idea of lifelong learning. The presented conceptualizations range from those linked to the performed profession, or the profession to which one should switch, to the latest conceptualizations, i.e., those in which lifelong learning encompasses various forms of education implemented throughout the individual?s life, from childhood to the retirement.
Keywords: lifelong learning; Polish-Czech-German borderland; NGOs; uczenie się przez całe życie; pogranicze polsko-czesko-niemieckie